The Effector AGLIP1 in Rhizoctonia solani AG1 IA Triggers Cell Death in Plants and Promotes Disease Development Through Inhibiting PAMP-Triggered Immunity in Arabidopsis thaliana - Li, Shuai; Peng, Xunwen; Wang, Yingling; Hua, Kangyu; Xing, Fan; Zheng, Yuanyuan; Liu, Wei; Sun, Wenxian; Wei, Songhong (Frontiers in Microbiology, 2019)
Rhizoctonia solani, one of the most detrimental necrotrophic pathogens, causes rice sheath blight and poses a severe threat to production. Focus on the function of effectors secreted by necrotrophic pathogens during infection has grown rapidly in recent years. However, little is known about the virulence and mechanisms of these proteins. In this study, we performed functional studies on putative effectors in R. solani and revealed that AGLIP1 out of 13 putative effectors induced cell death in Nicotiana benthamiana. AGLIP1 was also demonstrated to trigger cell death in rice protoplasts. The predicted lipase active sites and signal peptide of this protein were required for the cell death-inducing ability. AGLIP1 was greatly induced during R. solani infection in rice sheath. The AGLIP1's virulence function was further demonstrated by transgenic technology. The pathogenesis-related genes induced by pathogen-associated molecular pattern and bacteria were remarkably inhibited in AGLIP1-expressing transgenic Arabidopsis lines. Ectopic expression of AGLIP1 strongly facilitated disease progression in Arabidopsis caused by the type III secretion system-defective mutant from Pseudomonas syringae pv. tomato DC3000. Collectively, these results indicate that AGLIP1 is a possible effector that plays a significant role in pathogen virulence through inhibiting basal defenses and promoting disease development in plants.